Averroes' physics: a turning point in medieval natural philosophy - Glasner, Ruth (Oxford University Press, 2009)
Introduction : science through exegesis -- The complexity of Averroes' writing -- Description of the corpus -- The short commentary -- The middle commentary -- The long commentary -- The questions in physics -- The order of writing -- The changing cultural contexts -- Versions and revisions -- The short commentary -- The middle commentary -- The long commentary -- The late stratum of the long commentary -- The formal introduction -- The uses of syllogism -- The turning to alexander -- Averroes' new physics -- The turning point of Physics VIII : the breakdown of determinism -- The challenge of indeterminism -- Conflicting messages in Aristotle -- The story of the middle commentary -- The riddle of the long commentary -- The turning point of Physics VI : the breakdown of motion -- Introduction: The various concepts of motion in Aristotle's physics -- Aristotle's divisibility argument : a crack in the interval model of motion (Physics VI.4) -- Physics V reinterpreted : from homogeneity to heterogeneity -- Physics VI reinterpreted : from a continuous interval to a contiguous chain -- Physics III reintepreted : from dimensional entity toboundary entity -- When did the turning point occur? -- The turning point of Physics III : the breakdown of physical body -- Can physical body be a true homoeomer? -- Aristotle's moving-agent argument (physics VII.1) -- Alexander vs. Galen on the meaning of essentiality -- Averroes' notion of first-moved part -- Averroes' Aristotelian atomism -- The divorce between mathematics and physics -- When did the turning point occur?